Root and Canal Morphology of Mandibular Molars in a Selected Iranian Population Using Cone-Beam Computed Tomography - Madani, Zahra Sadat; Mehraban, Nika; Moudi, Ehsan; Bijani, Ali (Iranian Endodontic Journal, 2017)
Introduction: The aim of this study was to evaluate the root canal morphology of mandibular first and second molars using cone-beam computed tomography (CBCT) in northern Iranian population and also to indicate the thinnest area around root canals. Methods and Materials: We evaluated CBCT images of 154 first molars and 147 second molars. By evaluating three axial, sagittal and coronal planes of each tooth we determined the number of root canals, prevalence of C-shaped Melton types, and prevalence of Vertucci configuration and inter orifice distance. Also the minimum wall thickness of root canals was determined by measuring buccal, lingual, distal and mesial wall thicknesses of each canal in levels with 2 mm intervals from apex to orifice. Results: Amongst 154 first mandibular molars, 149 (96.7%) had two roots, 3 (1.9%) had three roots and 2 (1.2%) had C-shaped root configuration. Of 147 second mandibular molars, 120 (81.6%) had two roots, 1 (0.6%) had three roots and 26 (17.6%) had C-shaped roots. There was no significant difference in the prevalence of Vertucci’s type between two genders. The most common configuration in mesial roots of first and second molars were type IV (57%-42.9%) and type II (31.5%-28%). Mesial and distal walls had the most frequency as the thinnest wall in all levels of root canals with mostly less than 1 mm thickness. In second molars the DB-DL inter orifice distance and in first molars the MB-ML distance were the minimum. MB-D in first molars had the maximum distance while ML-DL, MB-DB and ML-D had the same and maximum distance in second molars. Conclusion: Vertucci’s type IV and type I were the most prevalent configurations in mesial and distal roots of first and second mandibular molars and the thickness of thinnest area around the canals should be considered during endodontic treatments. Keywords: Cone-Beam Computed Tomography; C-Shaped Root Canals; Mandibular First Molar; Mandibular Second Molar; Root Canal Anatomy; Root Canal Morphology